(untitled) (Journal of the College of Basic Education, 2022)
The Results of (FTIR) analysis indicated that the ethanolic extract of Tamarindus indica contain many active compounds like Hydroxamic, Saponin , Suger , Quinine and Alkaloids. The results of antibacterial activity which examined by well diffusion methods that the highly active to ethanolic extract on all pathogenic strains at different concentrations and the highest activity was (25) mm against Staphylococcus aureus at 0.1% ,also the warm water extract have good effectiveness against pathogenic strains at different concentrations and the highest activity was (12) mm against Staphylococcus aureus and compared the effectiveness of the biological extract with some antibiotics was observed all studied strains of antibiotic-resistant (Ampecillin, Erythromycim, Amoxicillin, Tetracycline) while all of them were sensitive to the ethanolic extract of the plant. The results in this study indicate that the Tamarindus indica have many active compounds and the fruit extract of plant possess higher antibacterial activity against different bacterial strains than antibiotics.